PERAN MASYARAKAT DALAM PELESTARIAN MATA AIR DI DESA BUDO KECAMATAN WORI KABUPATEN MINAHASA UTARA - Mariance Pansing; Hermon Maurits Karwur; Selvana T. R. Tewal (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
The research problem is what is the form of the community's role in preserving springs and what factors influence the community's role in preserving springs in Budo Village, Wori District, North Minahasa Regency. The research method used is qualitative research with the informants are the government, community leaders, and residents. The results of this study indicate that: The forms of the role of the people of Budo Village play a role in preserving the springs in the village, including 1) by providing motivation and direction to residents, 2) giving the advice to preserve the springs, 3) maintain cleanliness and sustainable 4) maintain survival and provide assistance funds, 5) Be active in community service activities and provide assistance as needed, 6) Take part in preserving springs and being active in site arrangement activities. Some factors encourage or influence so that the need for efforts to conserve springs in Budo Village, Wori District. The factors meant include 1) springs as village assets, 2) springs as a source of life, 3) water as necessities, 4) water is very important for the population.